Co-developing a short course on pastoralism and planetary health - Warsame, Rashid; Borthwick, Fiona (University of Edinburgh Royal (Dick) School of Veterinary Studies, 2025)
Presented at Building the Resilience and Prosperity of Pastoralists and Dryland Communities, Nairobi, Kenya, 1-2 October 2025
Keywords: drylands; pastoralism; capacity development; curriculum development; Kenya